How to get a job, by me, the boss - Lloyd-Jones, Sally, 1960-; Heap, Sue, 1954- (New York : Schwartz & Wade Books, 2011)
A young girl describes in detail how to decide on an interesting job and then tells exactly how to go about getting it.
2.8
K-3
K-3
Keywords: Occupations -- Juvenile fiction; Occupations -- Fiction; Occupations -- Fiction; Picture books for children